The effects of disturbance on the abundance and foraging behaviour of shorebirds and waterbirds in the tropical mudflat areas - Rosli Ramli,; Nor Atiqah Norazlimi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study was conducted in the mudflats of Jeram and Remis Beaches, Selangor, Peninsular Malaysia from November 2013 until July 2014 to determine the effects of disturbance on shorebird and waterbird abundance and foraging behavior. Direct observation was used in this study. Mann-Whitney test showed no significant difference in abundance of bird in Jeram and Remis Beaches (t=2.96, p=0.05). A significant difference were detected between the sampling plots in Jeram Beach (S=16.67, p<0.001) and Wilcoxon Signed Rank Test shows a significant difference between the sampling plots in Remis Beach (W=78, p=0.003). Spearman’s rank correlation shows significant association between the abundance of bird with the abundance of humans, dogs and vehicles (p<0.05) in both Jeram and Remis Beaches. Humans contribute to a higher percentage in disruptions towards the species studied (47.5%), followed by dogs (32.1%) and vehicles (20.4%). Thirty-six percent of birds stopped feeding and flew away upon disruption, 23% stopped feeding and run away, 22% stopped feeding but stay alert and 19% continue feeding (habituated). Analysis on the responses of birds toward the disturbance show significant difference between species (χ2 = 98.77, p<0.05). This study concluded that anthropogenic disturbance caused a major impact on shorebird and waterbird abundance and influenced their foraging behavior. Response of bird towards disturbance was varied according to the species and types of disturbance. By understanding how the bird species response toward disturbance, the conservation efforts can be implemented more effectively in the future.